The use of citrus pulp silage in Diplodus puntazzo nutrition - Silvia Nogales-Mérida; Ana Tomás-Vidal; Miguel Jover Cerdá; Nury B. Sánchez-Lozano; Jorge Velazco-Vargas; Silvia Martínez-Llorens (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose Studying the effect of citrus pulp silage in the growth performance, amino acid retention of sharpsnout sea bream juveniles. Methods Citrus pulp is an energy and protein source that has been used to replace wheat meal in Diplodus puntazzo fingerlings; 96 fish of 21.5 ± 0.67 g were nourished with two experimental diets for 105 days. The control diet (CON) contained 421.6 g/kg of protein and 22.6 MJ/kg of energy. The citrus pulp diet (CPD) included 442.7 g/kg of protein and 22.02 MJ/kg of energy. Results At the end of this trial, the CPD did not affect the growth parameters, but the feed efficiency values exhibited statistically significant differences, with those fish fed the CPD having higher values, possibly due to the presence of limonene in the diet. The CPD also resulted in a reduction in amino acid (AA) content due to the protein being bound to fibre; this consequence did not affect the final fish AA profile. For AA retention, only arginine displayed significant differences, although the rest of the AAs also showed effects of AA reduction from the CPD. Conclusion Citrus pulp silage can be used in D. puntazzo feeding, without adverse in the growth performance and the amino acid profile, although it did cause a reduction in feed efficiency.